Modification and Innovation of Flour-Based Products into Contemporary Pancong Cakes under the MBKM Program of Indo Global Mandiri University Students - Letari, Rahayu Tri; Hertati, Lesi; Asharie, Asmawati (CV. Proaksara Global Transeduka, 2023)
Pancong Cake is a traditional cake originating from Betawi, and the name